RURAL DEVELOPMENT TO CREATE INCLUSIVE ECONOMIC GROWTH - Ngurah Wisnu Murthi (Jurnal Ilmiah Satyagraha, 2024)
Rural development programs have been implemented in a number of ASEAN member countries, although as a separate priority and not as a complement to industrialization. These steps help increase growth and job creation in rural areas. This, in turn, paves the way for poverty alleviation in rural areas. The research objective that can be expressed is to analyze the influence of village development, village community creativity, BUMDes and creative economic efforts in the village, on the village's inclusive economic growth. The following conclusion was obtained: With accelerated village development, inclusive economic growth will be achieved in accordance with the ultimate goal of development. 1) By developing BUMDES in each village, business opportunities will be opened, absorbing labor and this will have an impact on the level of income and welfare of the community; 2) As the creativity of the village community increases, this will encourage village economic activities and have an impact on the village's original income and the economy of the village community. 3) Developing creative economic businesses as a way to open up job opportunities in the village by utilizing human resources in the village, so that this will increase family income and the village economy. The recommendation that can be given is that accelerating village development is very beneficial for village communities, especially in providing village infrastructure. Therefore, village development funding needs to be increased in order to foster: 1) village creativity, 2) BUMDES and 3) creative economic efforts, in order to increase inclusive economic growth in villages.